2022
DOI: 10.1371/journal.pone.0277544
|View full text |Cite
|
Sign up to set email alerts
|

Hypercoagulability in critically ill patients with COVID 19, an observational prospective study

Abstract: Objective COVID 19 is often associated with hypercoagulability and thromboembolic (TE) events. The aim of this study was to assess the characteristics of hypercoagulability and its relationship with new-onset TE events and the composite outcome of need for intubation and/or death in intensive care unit (ICU) patients admitted for COVID. Design Prospective observational study. Setting Monocentric, intensive care, University Hospital of Clermont Ferrand, France. Patients Patients admitted to intensive care… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 68 publications
0
5
0
Order By: Relevance
“…In addition, elevated fibrinogen and D-dimer levels were correlated with hypercoagulable states, inflammation, and unfavorable outcomes after COVID-19 [ 117 ]. The increased D-dimer paradoxically coincided with decreased fibrinolytic capacity [ 117 , 118 ].…”
Section: Disbalanced Endothelial-derived Hemostatic Regulators In Cov...mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, elevated fibrinogen and D-dimer levels were correlated with hypercoagulable states, inflammation, and unfavorable outcomes after COVID-19 [ 117 ]. The increased D-dimer paradoxically coincided with decreased fibrinolytic capacity [ 117 , 118 ].…”
Section: Disbalanced Endothelial-derived Hemostatic Regulators In Cov...mentioning
confidence: 99%
“…In addition, elevated fibrinogen and D-dimer levels were correlated with hypercoagulable states, inflammation, and unfavorable outcomes after COVID-19 [ 117 ]. The increased D-dimer paradoxically coincided with decreased fibrinolytic capacity [ 117 , 118 ]. Possibly, the presence of elevated D-dimer, especially during the early stages of pulmonary disease, could indicate the efforts of the local fibrinolytic system to eliminate fibrin and the necrotic tissue from the affected pulmonary parenchyma [ 118 ].…”
Section: Disbalanced Endothelial-derived Hemostatic Regulators In Cov...mentioning
confidence: 99%
“…Hypercoagulability, where blood tends towards heavy clotting, is particularly common after injury or infection, affecting approximately 1 in 500 people. [62][63][64] In normal blood, 0.06 mg/ml star-PSS slightly prolonged R and K and reduced a and MA, showing minor anti-coagulation effects without preventing viable clot formation (Figure 4C, turquoise triangles). At 0.1 mg/ml, clot strength was insufficient, although the typical clotting pattern was maintained (Figure 4C, yellow triangles).…”
Section: /21mentioning
confidence: 99%
“…Several studies have found a dose effect with an increased risk of myocardial infarction and death in patients with the elevated plasma fibrinogen levels [5]. Also, other diseases, such as infections and autoimmune diseases, can lead to an increase in fibrinogen levels [6][7][8]. During the systemic inflammatory process, high concentrations of cytokines appear, which are a trigger for the development of coagulopathy.…”
Section: Introductionmentioning
confidence: 99%